-11/9+1/2x-11/3x=3/2x-12/3-1

Simple and best practice solution for -11/9+1/2x-11/3x=3/2x-12/3-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11/9+1/2x-11/3x=3/2x-12/3-1 equation:


x in (-oo:+oo)

(1/2)*x-((11/3)*x)-11/9 = (3/2)*x-(12/3)-1 // - (3/2)*x-(12/3)-1

(1/2)*x-((11/3)*x)-((3/2)*x)-11/9+12/3+1 = 0

(1/2)*x+(-11/3)*x+(-3/2)*x-11/9+12/3+1 = 0

34/9-14/3*x = 0 // - 34/9

-14/3*x = -34/9 // : -14/3

x = -34/9/(-14/3)

x = 17/21

x = 17/21

See similar equations:

| 15y-18y+1y=-2+40-2 | | 4(x-3)=x+15 | | 21/7+(-7/4)-32/5 | | 182/n=13 | | (y^2-5y+3)(2y^2+7y-4)= | | 6(1+3m)=-9(-2m+5)-4 | | 11n=143 | | (-2/3)+8=(4/3)+6 | | -313/18=-3/2+2/3x | | (r^2)-7r-18=0 | | (-2/3x1)+8=(4/3x1)+6 | | 84/12=n | | 317/18=-1/2-5/3n | | -16=x+6 | | -7y-33=4y | | -53/12-8/12 | | 0.35/4.9x7=X | | 3(x+6)=x+2 | | -52/12-8/12 | | 4/7y+2/-8=-7 | | -4=3y-1+14 | | x^2+2x+(-3)=0 | | (2x-4)(2x+5)= | | 9.6=x/6 | | -5-(5y-1)=2(7y-16)-y | | 5z+32=4(2z+5) | | y/4-3=7 | | -8v-1=4v-1 | | w=1/4(x+y-z) | | -18-2x=36 | | 1/3x^2+4x-36 | | 3x(5y+38)(8x+26)= |

Equations solver categories